2019
DOI: 10.1007/s10661-019-7985-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of different solarisation systems and their impacts on soil thermal characteristics—an application in cultivated soils close to Baghdad, a highly populated city in Iraq

Abstract: Solarisation application by mulching the soil with a polyethene plastic film has a significant influence on soil thermal characteristics (TCs), which, in turn, show a strong impact on soil energy balance and agricultural productivity. In countries like Iraq with highly populated cities, such as Baghdad, that need large quantities of agriproducts, this kind of clean energy should play a key role in sustainable agricultural production. However, little is known about the effects of different soil solarisation sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
1
0
0
Order By: Relevance
“…In our trials, during the soil solarization, for all the cover plots, the heating treatment reported good results both at 10 cm and 30 cm depth whilst only at 10 cm depth, it was not very efficient for the uncovered thesis. This result is very similar those obtained in other solarization treatments [30,31].…”
Section: Soil Temperatures and Yield Responsesupporting
confidence: 92%
“…In our trials, during the soil solarization, for all the cover plots, the heating treatment reported good results both at 10 cm and 30 cm depth whilst only at 10 cm depth, it was not very efficient for the uncovered thesis. This result is very similar those obtained in other solarization treatments [30,31].…”
Section: Soil Temperatures and Yield Responsesupporting
confidence: 92%